2018 Chinese Automation Congress (CAC) 2018
DOI: 10.1109/cac.2018.8623233
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based Motion Planning For Autonomous Vehicle Using Spatiotemporal LSTM Network

Abstract: Motion Planning, as a fundamental technology of automatic navigation for autonomous vehicle, is still an open challenging issue in real-life traffic situation and is mostly applied by the model-based approaches. However, due to the complexity of the traffic situations and the uncertainty of the edge cases, it is hard to devise a general motion planning system for autonomous vehicle. In this paper, we proposed a motion planning model based on deep learning (named as spatiotemporal LSTM network), which is able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…s t as in equation (16) or (23). Then we use the trained policy w π to make real-time decisions by equations (14) and (15). In the aspect of motion planning, as the decisions have included the longitudinal speed information, we only concern about the lateral trajectory planning by equation (26), i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…s t as in equation (16) or (23). Then we use the trained policy w π to make real-time decisions by equations (14) and (15). In the aspect of motion planning, as the decisions have included the longitudinal speed information, we only concern about the lateral trajectory planning by equation (26), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Kernel-based API in [8] and ELM-API in [9] dealt with simple overtaking tasks and lane-change issues without considering the trajectory planning when there exists the obstacles. In [10]- [14], deep learning approaches were used for training the collected raw sensor samples in specific scenarios which can map the images to actions. The advantages of using deep neural networks include automatic feature extraction and feature representation.…”
Section: Related Work and Research Background A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are many approaches to road prediction using LSTM architectures for this type of forecasts. Bai et al [67], suggested spatiotemporal LSTM architecture for motion planning in AVs. It uses convolutional layers for feature extraction in an image, and it runs through an LSTM to find sequences in those images, something similar to a CRNN architecture.…”
Section: Lstm Based Modelsmentioning
confidence: 99%
“…Another class of methods focuses on learning driving policy from raw sensor inputs, such as those from cameras, LIDAR and screen shots of a simulator [3][4][5][20][21][22]. Sallab [20] et al proposed a new framework of DRL for autonomous vehicles, which combines LSTM and attention networks to capture the spatial features.…”
Section: Introductionmentioning
confidence: 99%